The Cabala - Wilder, Thornton, 1897-1975 (Salt Lake City, UT : Project Gutenberg, 2022)
"The Cabala" by Thornton Wilder is a novel written in the early 20th century. The story is set primarily in Rome and introduces a tapestry of characters embroiled in social intrigue, particularly focusing on a mysterious and elite group referred to as the Cabala. The main characters include a young American named James Blair, who becomes entangled in the lives of these affluent intellectuals, and his enigmatic companion, Miss Grier, who plays a pivotal role in the circles of influence in which they revolve. At the start of the novel, the protagonist arrives in Rome, overwhelmed by the city's rich history, only to find himself on a crowded train filled with a diverse array of passengers, each with their own stories. As he settles into his life in the city with guidance from Blair, he learns about the Cabala$1 (Ba wealthy, powerful group that garners both admiration and fear from the society around them. The intriguing dynamics of this group are unveiled through conversations and interactions, suggesting that their influence extends into the political and social realms, yet they also face internal struggles and existential boredom. The opening sets the stage for a deeper exploration of themes related to wealth, power, and the search for meaning within the influential echelons of society. (This is an automatically generated summary.)s
Release date is 2022-05-17
Laura Natal Rodrigues (Images generously made available by Hathi Trust Digital Library.)
Keywords: Upper class -- Fiction; Rome (Italy) -- Social life and customs -- 20th century -- Fiction; Americans -- Italy -- Fiction